O turismo nas ondas do litoral e das políticas públicas do Piauí - Maria Majaci Moura da Silva (2013)
This thesis aims to analyze the integration of policies targeting tourist activity off the coast of Piauí, from the socio-economic and environmental outcomes for the people and residents in relation to governance, and the generation of employment and local improvements, as well as analyze the situation of Piauí in the script Route of Emotions and especially, propose strategic actions for the management of tourism . We sought to understand why the Delta river with all the beauty and uniqueness that has articulated the script Route of Emotions, strategically, can change the scenario of tourism comparing to neighbors, Ceará and Maranhão states. We selected the Polo Delta Coast, making a spatial area of the four coastal municipalities piauienses: Parnaíba Luis Correia, Cashew Beach and Ilha Grande, highlighted by presenting within the tourism sector in the state and this activity is the main axis of growth and consolidation of the region. The methodology was divided into two stages: the exploratory and qualitative. The semi-structured interviews took place during 12 field visits, initiated in July 2009 and completed in May 2013. This step comprised 20 face interviews with municipal managers and 88 taken with students, businessmen, politicians NGO leaders and teachers in tourism on the coast , beyond the bibliographic and documentary analysis . For aspects related to collection and analysis of data, appropriated the techniques of SWOT, and analysis of content. The results confirmed the need to improve the sustainability indexes of tourism, with a view mainly to poor infrastructure as a result of poor public policies for tourists and residents on the coast of Piauí. Comes to the conclusion that socioeconomic difficulties of Piauí are responsible for the delay of the development of tourism policies, manifested in high rates of unemployment and underemployment, due to the high rate of illiteracy and poverty, which causes an increase in crime, delinquency and trafficking and drug use , the public policies implemented in Piauí, are quite fragile, benefiting mega projects , and it is found the discontinuity of projects in the area of construction, coupled with the lack of basic infrastructure, lack of security and low quality of services directly related to the tourism sector.